A study on the surgical management of abdominal tuberculosis in patients attending a tertiary hospital - Yogish, Vikram; Grover, Himanshi; Joseph, Sunu Ancy (International Surgery Journal, 2020)
Background: Tuberculosis is seen due to various factors such as overcrowding and unhygienic conditions. In order to diagnose a case of abdominal tuberculosis, a detailed history and a thorough clinical examination must be done. The objective of this article was to determine the number of patients who presented to a tertiary hospital with abdominal tuberculosis and in which of these patients management in the surgical department was required. Methods: A total of 50 patients who had abdominal tuberculosis were studied. The study was carried out at SRM Medical College Hospital and Research Center, Kattankulathur, Tamil Nadu, India. The study was carried out from February 2017 to January 2020. A detailed history was obtained and a thorough clinical examination was done. Investigations such as CBC, chest X-ray, abdomen X-ray, ultrasound scan and CT scan of the abdomen were done. When required, patients underwent surgery and the results obtained were analyzed and tabulated. In our study, out of a total of 50 patients, 32 patients were found to have required surgery. The statistics were analyzed using SPSS package 16.0. Results: It was seen that in this study, male patients were more commonly affected with abdominal tuberculosis, and resection and anastomosis was the most common surgical procedure done when required. The findings obtained were compared with other studies. Conclusions: In patients with abdominal tuberculosis, a detailed history and a thorough clinical examination are required in order to diagnose the condition as early as possible.